Саяси белсенділікті арттырудағы фактор ретінде сайлау жүйесі (Journal of Philosophy, Culture and Political Science, 2018)
Article is devoted an electoral system as to the factor of increase of political activity. The author carries out the comparative analysis of political activity in the conditions of two basic electoral systems: majority and proportional, experience of their use in Kazakhstan.